PHYSICO-CHEMICAL ANALYSIS OF POWER PLANT EFFLUENT DISCHARGE ON EKEMAZU STREAM IN DELTA STATE, NIGERIA. - Hilda Emmanuel-Akerele (Hasanuddin University, 2022)
Physicochemical analysis of Ekemazu stream in Delta State, Nigeria was carried out to assess the water quality between September 2014 and June 2015. Physicochemical parameters were analyzed according to standard methods for examination of water and wastewater. The turbidity of all the samples analysed across the seasons showed that the value was highest at the effluent discharge point at the peak of the flood season and least in the upstream at the setting – in of raining season in the following range: upstream; 12 ± 1 NTU to 25 ± 0 NTU, effluent discharge point; 121 ± 0 NTU to 423 ± 39 NTU, domestic activities point; 85 ± 2 NTU to 373 ± 40 NTU and in the downstream; 70 ± 0 NTU to 341 ± 44 NTU. All other parameters analyzed followed similar trend (highest in the effluent discharge point) either during the peak of flood season or peak of raining season and least in the upstream sample at other seasons. The statistical analysis of the difference in the physicochemical parameters of the upstream samples and the values obtained in effluent discharge point, domestic activities point and the downstream were all significant (P<0.05). This research clearly showed that some physicochemical parameters of the stream are higher than the WHO acceptable limit. This is due to the release of heavily polluted effluent into the stream, seasonal variations as well as some human activities in the water body resulting to high pollution of the stream.